ISOLASI DAN KARAKTERISASI BAKTERI PENDEGRADASI PESTISIDA DICOFOL DARI TANAH SAWAH DI KABUPATEN KARAWANG - Anindita Ayu Pratiwi; Agung Suprihadi; Budi Raharjo; Priyo Wahyudi; Sih Parmiyatmi (Jurnal Akademika Biologi, 2012)
Karawang was the center of rice production, but rice production in paddy fields in Karawawang often faces obstacle hopper pest that caused crop failure. These condition prompted the farmers to using dicofol pesticides excessively, thus caused pollution of pesticides. The purpose of this research were get the isolates bacteria that could degrade the pesticide dicofol in Karawang paddy fields and discovered characteristics of bacteria that have potential to degrade pesticides. The research was conducted with the isolation and characterisation of bacteria from Karawang paddy soil, the characterisation of isolates bacteria by observation morphological and phenotypic include staining Gram and biochemical tests, test isolates bacteria resistence of dicofol, measuring the growth curve and High Performance Liquid Chromatography (HPLC) for discovering of decreased dicofol concentration during 24, 48, and 72 hours of incubation time. The result is six isolates, that are AA1, AA2, AA3, AA4, AA5, and AA6. Isolates AA1 is suspected as genus Phenylobacterium, isolates AA3 and AA6 are suspected as genus Pseudomonas, AA4 isolates is suspected as genus Bacillus, isolates AA5 is suspected as genus Alcaligenes, but isolates AA2 not yet be identified. The results indicate that isolate AA6 has most resistent to dicofol and most number of cells bacteria, that is 7.9x108. Isolate AA6 is also the most effective in degrading dicofol as much as it can reduce the concentration in amount of 76.0 ppm (84.45%) in MSM medium + 90 ppm dicofol. Keywords : Isolation, Characterisation, Bacteria, Resistention, Degradation, Dicofol Pesticide